PENERIMAAN PANELIS DAN ANALISIS USAHA ROTI MANIS DARI TEPUNG TERIGU DAN MODIFIED CASSAVA FLOUR (MOCAF) - Aryati, Dini Sri; Ali, Akhyar; ', Eliza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purposes of this study were to analyse the level of acceptance by the panelists and to analyze the business feasibility of sweet bread made from wheat and modified cassava flour (mocaf). the research was conducted experimentally by making sweet bread from 70% wheat and 30%mocaf and then tested the panelists acceptance and business analysis. Method was use accepted test by 50 panelists tested the sweet bread and then calculates by Cochran’s Q test. Accepted test by 50 panelists whose 43 panelists accepted the experience sweet bread and 49 panelists accepted the commercial sweet bread. Cochran’s Q test shows that F table is lower than F calculating, therefore sweet bread from wheat and mocaf was different with commercial sweet bread. Total cost of a day processing production from 5 kg powders were Rp. 245.985,21 with 307 sweet breads and sell with price is Rp. 1.000,00 answered is Rp. 307.000,00 revenue. Benefit that got is Rp. 61.014,79 with efficience of business is 1,25. Total product of break even point were 246 sweet breads with minimal priced is Rp. 801,25. Total product and price of break even point which important point to make this business was not failed. Conclusion of this experience is sweet bread could be accepted by panelist and ready to sell. Keywords: business analysis, mocaf,panelists acceptance, sweet bread, wheat